An unusual case of duodenal metastasis of pulmonary pleomorphic carcinoma - Ustaoğlu, Müge; Koçak, Gülgün; Siviloğlu, Çiğdem; Cengiz, Ercüment (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Ustaoğlu M, Koçak G, Siviloğlu Ç, Cengiz E. An unusual case of duodenal metastasis of pulmonary pleomorphic carcinoma. Turk J Gastroenterol 2018; 29:132-3.